Duchowe zmysły. Percepcja Boga w zachodnim chrześcijaństwie, red. Paul L. Gavrilyuk – Sarah Coakley, tłum. Aleksander Gomola, Kraków 2014, Wydawnictwo WAM, ss. 392. - Klusek, Kacper (Vox Patrum, 2018)
nie dotyczy